(untitled) (Research, Society and Development, 2022)
During labor, the parturient requires pelvic mobility and intensive use of the muscles of the abdomen, perineum and respiratory diaphragm. Therefore, the physical therapist is able to deal with the multiple musculoskeletal changes that occur in response to pregnancy. The present study aims to discuss the benefits of physical therapy in childbirth and puerperium. This is a bibliographic review, in which articles were searched in the following databases: Medical Literature Analysis and Retrieval System Online and Latin American and Caribbean Literature on Health Sciences, using the Health Sciences Descriptors: Physiotherapy; Parto and Puerperio, crossed with the Boolean operator AND. After applying the inclusion and exclusion criteria, all 10 documents were left to be included in the research. The physiotherapeutic guidelines aimed at reducing the discomforts and difficulties of the puerperal woman, solving doubts and helping to increase the woman’s confidence in relation to her own body. Considering that most interventions carried out in this period focus on guidelines related to the care of the newborn, and not on clarifying the woman’s doubts regarding care for herself, which can cause dissatisfaction in the postpartum phase. It is concluded that, given the data collected, that physiotherapy is of paramount importance in the hospital environment and it is worth mentioning the benefits of providing the care offered to pregnant and postpartum women.